Knowledge Sharing in Private Finance Initiative (PFI) Project in Sarawak - Mohd Shamsul, Noremiza; Kipli, Kumalasari; Zaini, Favilla; Jasni, Mohd Dzuliqyan; Mustapa, Fara Diva (Research in Management of Technology and Business, 2024)
Private Finance Initiative or PFI is still considered a new procurement in the Sarawak construction industry because most people still do not know the concept of a PFI project. Simply put, PFI is a contract based on Built Maintain Lease Transfer (BMLT). PFI projects also have a different construction period than conventional contracts, where a PFI project typically takes 20-25 years to complete. To ensure that this project can be completed, good knowledge of management is needed. Good knowledge management can be derived from how the parties involved in this project share their knowledge, essentially with the customers, in this case, UiTM and the concession parties. This research focuses on the sharing of knowledge in the facilities and maintenance stage. The methodology adopted in this research was the qualitative method, namely interviews. The respondents consist of two facilities managers and two civil engineers. The findings show that there are three methods of knowledge sharing: mentoring, face-to-face, and using IT currently used in knowledge sharing for the two PFI projects, which are the UiTM Sarawak, Samarahan 2 Campus and UiTM Sarawak, Mukah Campus